(untitled) (Archives of Clinical Psychiatry, 2019)
Objective: Not only white blood cells but also platelets are being considered in inflammatory reactions from now on. Mean platelet volume (MPV) and neutrophil to lymphocyte ratio (NLR) have been shown to change in inflammatory diseases like myocardial infarction, stroke and implicated in psychiatric disorders nowadays. Our first aim is to investigate the relation of MPV and NLR with depression and secondly to assess if they change with the treatment of depression. Methods: Forty-nine patients diagnosed with major depressive disorder (MDD) and hospitalized in a university hospital psychiatry inpatient unit retrospectively included in the study. Control group consisted of 48 hospital workers with no known disease. Complete blood count, Hamilton Depression Rating Scale (HAM-D) and Clinical Global Impression-Severity Scale (CGI-S) scores at admission and at discharge were noted and compared for the patient group. Discussion: MPV of depressed patients was higher than controls. When we look at admission and discharge scores of clinical scales, decrement is statistically significant for both HAM-D and CGI-S. There was decline both in MPV and NLR which were both statistically significant. Conclusion: Decreasing MPV and NLR values with the treatment of depression confirm the involvement of inflammatory processes in the pathophysiology of depression.